Dampak Jam Kerja Fleksibel Terhadap Motivasi, Kepuasan, dan Kinerja Pegawai Setjen MPR-RI - Pohan, Adam Arifin; Yosepha, Sri Yanthy (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study aims to determine the impact of the implementation of flexible working hours on motivation, satisfaction, and performance at the Secretariat General of the MPR RI Methodology/approach: The type of research used is descriptive qualitative, and the informants in the study were 4 people. Results/findings: The employees of the Secretariat General of the MPR RI have the same perception that the establishment of flexible working hours can improve employee performance organizational environment. The implementation of flexible working hours has a positive impact on employee motivation, satisfaction and performance. Conclusion: The implementation of flexible working hours has significant potential to improve the motivation, satisfaction, and performance of Secretariat General of the MPR RI employees, although it requires careful management of the constraining factors. Limitations: This research only focuses on the implementation of flexible working hours that can affect employee motivation, satisfaction, and performance, and is limited to the scope of the Secretariat General of the MPR RI. Contribution: This research provides a deeper understanding of the dynamics of flexible working hours implementation in the context of government organizations in Indonesia, especially the Secretariat General of the MPR RI, and offers practical recommendations for more effective and adaptive policy development.